Design of High Average Power OPCPA Based on Simultaneous Temperature and Wavelength Insensitive Phase Matching - Daolong Tang; Jing Wang; Jingui Ma; Bingjie Zhou; Peng Yuan; Guoqiang Xie; Liejia Qian (IEEE Photonics Journal)
Optical parametric chirped-pulse amplification (OPCPA) provides an efficient route to push ultrafast pulses toward ultrahigh peak powers. However, in high average power regime, the unavoidable thermal effects in nonlinear crystals will intrinsically destroy the phase-matching (PM) condition, which fundamentally limit average power scaling. Here, we present a theoretical design of high average power OPCPA based on simultaneous temperature and wavelength insensitive PM. By regulating the temperature set for PM as well as the wavelength of interacting waves in lithium triborate crystal, the noncollinear angles for temperature insensitive PM and wavelength insensitive PM will coincide and thus ensures simultaneous temperature and wavelength insensitive PM condition. We investigate the performances of the proposed PM scheme in comparison with traditional wavelength insensitive noncollinear PM. Because of the larger temperature bandwidth, higher average power can be anticipated in OPCPA with the proposed PM scheme. Besides, the large spectral bandwidth also allows the amplification of sub-10 fs pulses in the visible spectral range. The proposed PM scheme will provide a promising approach in generating ultrashort pulses with high peak and average powers.